1995
DOI: 10.1007/bf00931793
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-gamma levels during the course ofTrypanosoma cruzi infection ofCalomys callosus (Rodentia-Cricetidae) and Swiss mice

Abstract: Serum levels of interferon-gamma (IFN-gamma) were evaluated in Calomys callosus and Swiss mice during the course of infection by four strains of Trypanosoma cruzi. All strains stimulated the production of this interleukine; however, the timing of its onset and permanence varied among strains and between the two animal models. When chronically infected animals with no detectable serum IFN-gamma were challenged with the homologous strain, they produced quantities comparable with those obtained during the acute p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
12
0

Year Published

1997
1997
2006
2006

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 43 publications
3
12
0
Order By: Relevance
“…These observations were associated with in situ expression of TNF-α and IFN-γ. Probably the TNF-α and IFN-γ are mediating parasite disintegration by macrophage activation, with release of O metabolites such as H 2 O 2 , as demonstrated by Borges et al (1995). In the present study it has been demonstrated that IFN-γ persists in C. callosus tissues for a prolonged time (65 days) as compared with the other cytokines that were absent in the heart and skeletal muscle at this phase.…”
Section: Discussionsupporting
confidence: 62%
See 4 more Smart Citations
“…These observations were associated with in situ expression of TNF-α and IFN-γ. Probably the TNF-α and IFN-γ are mediating parasite disintegration by macrophage activation, with release of O metabolites such as H 2 O 2 , as demonstrated by Borges et al (1995). In the present study it has been demonstrated that IFN-γ persists in C. callosus tissues for a prolonged time (65 days) as compared with the other cytokines that were absent in the heart and skeletal muscle at this phase.…”
Section: Discussionsupporting
confidence: 62%
“…In previous studies (Borges et al 1995), evaluation of IFN-γ levels in C. callosus infected with T. cruzi, was performed by titration of antiviral activity on L-929 cells, by using a stan-dard encephalomyocarditis virus cytopathic-effectinihibiton. To characterize the antiviral activity, serial dilutions of serum samples were incubated with anti-murine IFN-γ monoclonal antibody.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations